Temporal analysis of land use and cover in an urban watershed in the city of Londrina / PR - Chang, Mein Mieko; Pinheiro, Hemerson Donizete (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
This study analyzed the changes in land use and cover of Ribeirão Cambé watershed (Londrina /PR), between 1975 and 2015, and evaluated how these changes impact on the runoff volume. For the classification of soil use and cover were used satellite images from the Landsat series (1-MMS, 5-TM and 8-OLI), which were acquired for free from the INPE/DGI website. The classification was made by the SPRING program, it was used to establish four themes of soil use and cover: urban, dense vegetation, underbrush and exposed soil. The CN value was obtained from the CN tables of SCS for urban and suburban basins. Morphological characterization of Ribeirão Cambé basin indicates low probability of flooding. Using satellite images, it was possible to affirm that significant changes happened in the soil use and cover of this basin, having grown 150% in 40 years, with the highest growth rates occurring in the first analyzed decades, 42%, 33%, 18% and 11%, respectively. Thus, the conclusion is that changes in soil use and cover in river basins reflect on the runoff, evidentiating the need of discussion about urban planning and flood control.